The efficacy of postoperative radiotherapy in localized primary soft tissue sarcoma treated with conservative surgery. Issue 1 (December 2016) - Zhao, Ru-Ping; Yu, Xiao-Li; Zhang, Zhen; Jia, Li-Juan; Feng, Yan; Yang, Zhao-Zhi; Chen, Xing-Xing; Wang, Jian; Ma, Sheng-Lin; Guo, Xiao-Mao
Abstract Background To evaluate the efficacy of postoperative radiotherapy (RT) on local failure-free survival (LFFS), distant metastasis-free survival (DMFS) and overall survival (OS) in patients with localized primary soft tissue sarcoma (STS) and to identify prognostic factors. Methods and materials Between January 2000 and July 2010, 220 consecutive patients with localized primary STS, who received conservative surgery with or without postoperative RT, were enrolled in the study. Survival curves were constructed by the Kaplan-Meier method and log-rank test was used to assess statistical significance. Multivariate analysis was applied to identify the prognostic factors. Results After a median follow-up of 68 months (range, 5–127 months), the 5-year LFFS, DMFS and OS were 70.0, 78.2 and 71.2 %, respectively. Tumor size, histological subtypes, margin status and postoperative RT were independent predictors for OS. Postoperative RT was associated with a significant reduced local recurrence risk versus surgery alone (hazard ratio [HR] = 0.408, 95 % confidence interval [CI] 0.235–0.707, P = 0.001), with 5-year LFFS of 81.1 and 63.6 %, respectively (log-rank, P = 0.004). The log-rank test showed that postoperative RT had a tendency of improving OS compared with surgery alone, with 5-year OS of 74.8 and 65.0 %, respectively (P = 0.089). Multivariate analysis demonstrated that postoperative RT significantly reduced mortality rate compared with surgery alone (HR = 0.512, 95 % CI 0.296–0.886, p = 0.017), especially in patients with liposarcoma (p = 0.034). Conclusion Postoperative radiotherapy reduce both local recurrence and STS mortality in patients with localized primary STS. The efficacy of RT on survival warrants further prospective study.